Retinal projection head-mounted display - LIN, Junguo; CHENG, Dewen; YAO, Cheng; WANG, Yongtian (Frontiers of Optoelectronics (Online), 2017)
Retinal projection displays （RPDs） are an important development direction for head-mounted dis- plays （HMDs）. This paper reviews the literature on optical engineering aspects based on the data on advanced technology in RPD design and development. The review includes the principles and applications of four theories, e. g., the Maxwellian view and its modified modality and the monocular and binocular depth cues of stereoscopic objects in the physiology of the human visual system. To support the Maxwellian view and achieve retinal projec- tion systems with depth cues, results of previous design works were summarized using different methods and their advantages and disadvantages are analyzed. With an extremely long focal depth, a prototype of a full-color stereoscopic see-through RPD system was discussed. Finally, a brief outlook of the future development trends and applications of the RPDs was presented